A Twisted Phosphor: Breaking T1 Energy Conservation in Dopant‐Matrix Organic Phosphorescence Systems. Issue 4 (14th December 2022) - Ding, Shuhui; Wang, Xuepu; Wang, Guangming; Wu, Minjian; Li, Junbo; Zhao, Xiaoya; Li, Haodong; Ren, Shixue; Zhang, Kaka
Abstract: In the exciton model of organic compounds proposed by Kasha, energy levels of T1 states are insensitive to microenvironment because of negligibly small transition dipole moments of T1 states. This phenomenon of T1 energy conservation holds true in most organic systems. Here a serendipitous finding of a twisted organic phosphor that breaks T1 energy conservation in dopant‐matrix phosphorescence systems is reported. Specifically, the twisted phosphor exhibits distinct phosphorescence colors and T1 energy levels when doped into different organic matrices under ambient conditions. Time‐dependent density functional theory calculations reveal that, when the twisted phosphor is in its freely rotating form, the increase of twisted angle leads to the increase of its T1 energy level. After being planarized by alkyl cyclization, the phosphor shows the recovery of T1 energy conservation. Owing to its sensitive T1 level, the twisted phosphor functions as label‐free and visual probe for direct observation of polymer phase separation. Abstract : Kasha's excitons model proposes that organic T1 energy levels are insensitive to microenvironments because of their negligibly small transition dipole moments. This description of T1 energy conservation holds true in most organic systems. Here the twisted phosphor exhibits distinct phosphorescence colors in different organic matrices, breaks T1 energy conservation, and functions as label‐free probe for polymer phase separation observation.